The Binding Force of The Droit Suite Principle in Land Pledge Regarding The Object of Encumbrance Right - Rifai, Achmad (Journal of Private and Commercial Law, 2023)
The objective of this research is to analyze the legal protection for the holder of the Right of Encumbrance after the encumbered object of the Right of Encumbrance has been tied to the Customary Land Pledge by the grantor of the Right of Encumbrance. The method employed in this research is normative legal research with a statutory approach and within the scope of customary law. The research outcomes can be summarized as follows: the grantor of the Right of Encumbrance (debtor) can transfer the object of the Right of Encumbrance to the holder of the Customary Land Pledge (third party) because there are two provisions in obtaining a loan from guarantee institutions, namely Law Number 4 of 1996 concerning Encumbrance Rights over Land and Related Objects and Government Regulation in Lieu of Law Number 56 of 1960 concerning the Determination of Agricultural Land Area. Therefore, the principle of droit de suite, or as a property right, provides legal protection for the holder of the Right of Encumbrance (creditor) regarding the transfer of collateral objects with Customary Land Pledge, which is of a personal nature, resulting in the non-binding of debt repayment on the pledged collateral object that was previously encumbered with the Right of Encumbrance.